(untitled) (Plant Tissue Culture and Biotechnology, 2025)
Dendrobium transparens is an endangered medicinal and ornamental orchid species of Bangladesh. The nodal segments of in vitro grown plantlets were used as explant for this study. MS medium provides the highest percentage (85.0 ± 0.37) of primary (PLBs) formation. While the highest percentage of secondary PLBs (88.0 ± 0.58) and its maximum weight (1.15 ± 0.05g) was recorded when the cultures medium were fortified with 2.0 mg/l Kn + 1.0 mg/l NAA. The maximum percentage of shoots (80.0 ± 0.45) were recorded when 0.5 mg/l BAP was used. The highest length (4.34 ± 0.10 cm) of plantlets was found when the medium was enriched with 2.0 mg/l BAP and 1.0 mg/l NAA. The maximum number of multiple shoot buds (MSBs) (9.60 ± 0.15) was recorded on a medium containing 1.5 mg/l BAP + 0.75 mg/l NAA. Following acclimatization well rooted plantlets were shifted to the orchid shed house of the Institute of Biological Sciences (IBSc), University of Rajshahi. The protocol established during this study might be very useful for mass multiplication and further improvement of orchids in Bangladesh. Plant Tissue Cult. & Biotech. 35(1): 81-91, 2025 (June)